x+9=11x-1

Simple and best practice solution for x+9=11x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+9=11x-1 equation:



x+9=11x-1
We move all terms to the left:
x+9-(11x-1)=0
We get rid of parentheses
x-11x+1+9=0
We add all the numbers together, and all the variables
-10x+10=0
We move all terms containing x to the left, all other terms to the right
-10x=-10
x=-10/-10
x=1

See similar equations:

| 2x+3=3x−1 | | a/5-4=16 | | 12.12=2g+3.74 | | 9(11)+25+17y+15=180 | | -20=3/2w | | 4/3x-4/3=-1/3x-1/2 | | 7v-36=5(v-8) | | -8+4m=-2 | | 5=3/5t | | 510+80x=590+60x | | 12x-6=3(4x-2) | | 0.15(y-0.2=0.5(y-1) | | (3x+12)/4=0 | | 1/3(1x-24)=16 | | 8=s/3 | | F(x)=-2x2-4x6-3x3-8 | | 5x+7+3x=13 | | 7(4x-5)-4(6x+5=-91 | | 15x-10x=30-5 | | -3x10=x+6 | | 3(x+6)=3(x-6) | | 3(2-4x)=80 | | 8=14a | | 36+9x=63 | | 2(x+5=-(x+2) | | 2.4+10m=7.23 | | 3/5(15c+10)=12c–9 | | 46−=−nn | | -14-2x=16+3x | | 36=-12x+36 | | 14x-4=-46 | | 0=5(t-2)^2-7(t-2)+7 |

Equations solver categories